(untitled) (Ordia Prima, 2024)
Parrhesia, freedom of thought and freedom of speech, is one of the foundations, first of all, of the idea of democracy. It was born from the first experiments of democracy in Athens in the 5th century BC. For us there is no freedom, there is no equality, if there are not these freedoms to think and say everything in front of everyone. Free speech, critical speech, the multiplicity of thoughts and voices are essential principles. No one can say that he possesses the truth, no one can impose his unique thought, his dogma. It is the first antidote to autocracy. Here then parrhesia serves to discuss the conventions, inertia and encrustations of every society. It can unmask any propaganda, any mystification, any illusion. Achilles, between the Iliad, the Odyssey and Lucian’s Dialogues of the Dead, is perhaps our first archetype, against the errors and power of Agamemnon, but also against the illusions and conventions of heroic ethics.